Generation of GGTA1−/−β2M−/−CIITA−/− Pigs Using CRISPR/Cas9 Technology to Alleviate Xenogeneic Immune Reactions. Issue 8 (August 2020) - Fu, Rui; Fang, Minghui; Xu, Kai; Ren, Jilong; Zou, Jun; Su, Long; Chen, Xinxin; An, PeiPei; Yu, Dawei; Ka, Meina; Hai, Tang; Li, Ziyi; et al.
Abstract : Background: Xenogeneic organ transplantation has been proposed as a potential approach to fundamentally solve organ shortage problem. Xenogeneic immune responses across species is one of the major obstacles for clinic application of xeno-organ transplantation. The generation of glycoprotein galactosyltransferase α 1, 3 ( GGTA1 ) knockout pigs has greatly contributed to the reduction of hyperacute xenograft rejection. However, severe xenograft rejection can still be induced by xenoimmune responses to the porcine major histocompatibility complex antigens swine leukocyte antigen class I and class II. Methods: We simultaneously depleted GGTA1, β2-microglobulin ( β2M ), and major histocompatibility complex class II transactivator ( CIITA ) genes using clustered regularly interspaced short palindromic repeats and CRISPR-associated proteins technology in Bamma pig fibroblast cells, which were further used to generate GGTA1 −/− β2M −/− CIITA −/− triple knockout (GBC-3KO) pigs by nuclear transfer. Results: The genotype of GBC-3KO pigs was confirmed by polymerase chain reaction and Sanger sequencing, and the loss of expression of α-1, 3-galactose, SLA-I, and SLA-II was demonstrated by flow cytometric analysis using fluorescent-conjugated lectin from bandeiraea simplicifolia, anti-β2-microglobulin, and swine leukocyte antigen class II DR antibodies. Furthermore, mixed lymphocyte reaction assay revealed that peripheral blood mononuclear cells from GBC-3KO pigs were significantly less effective than (WT) pig peripheral blood mononuclear cells in inducing human CD3 + CD4 + and CD3 + CD8 + T-cell activation and proliferation. In addition, GBC-3KO pig skin grafts showed a significantly prolonged survival in immunocompetent C57BL/6 mice, when compared with wild-type pig skin grafts. Conclusions: Taken together, these results demonstrate that elimination of GGTA1, β2M, and CIITA genes in pigs can effectively alleviate xenogeneic immune responses and prolong pig organ survival in xenogenesis. We believe that this work will facilitate future research in xenotransplantation. Abstract : Supplemental Digital Content is available in the text.